HUBUNGAN ANTARA DUKUNGAN KELUARGA TERHADAP KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET ZAT BESI DI KLINIK BERSALIN BIDAN NANI S AMKeb - Fitriyani Nasution (Akademi Kebidanan Ika Bina, 2022)
Anemia is one of the health problems that often occurs in every woman, especially for women who are pregnant, this is due to less consumption of blood-boosting tablet supplementation and the non-adherence of pregnant women to consume iron tablets. The factor that causes non-compliance in consuming this blood booster tablet is the lack of family support. This study aims to determine the relationship between family support and maternal compliance in consuming iron tablets at the Midwife Nani S Amkeb Maternity Clinic. This type of research uses an analytical survey method with a Cross Sectional approach. The research was carried out at the Midwife Nani S Amkeb Maternity Clinic. The population in this study were mothers who were pregnant who did an examination at the Midwife Nani clinic as many as 52 people. The data obtained from the data from the questionnaire. Data analysis in this study was univariate and bivariate with Chi Square data test. The results showed that high family support (61.54%) low family support (38.46%), while adherence to consuming iron tablets in obedient mothers (53.85%) and pregnant women who did not comply with consuming iron tablets. iron (46.15%). The test results of the analysis of the relationship between family support and adherence to consuming iron tablets using the Chi-Square calculation showed that the significant value of p = 0.000 < (0.05) this means that Ha is accepted. And it can be concluded that there is a relationship between family support and adherence to consuming iron tablets at the Midwife Nani S Amkeb Maternity Clinic